The Limits of Social Recognition: Experimental Evidence from Blood Donors - Lorenz Goette; Egon Tripodi (Ludwig-Maximilians-Universität München und Humboldt-Universität zu Berlin, Collaborative Research Center Transregio 190 - Rationality and Competition, 2023)
Does social recognition motivate prosocial individuals? We run large-scale experiments at Italy's main blood donors association, testing social recognition in social media and peer groups. We experimentally disentangle visibility concerns and peer comparisons, and study how exposure to different social norms affects giving. In three studies, we find that a simple ask to donate is at least as effective as offering social recognition. A survey experiment with blood donors indicates that social recognition backfires when offered to people that are already perceived as good citizens. Our results suggest that increasing visibility of good actions can backfire when perceived as image-seeking.
Keywords: C93; D91; 330; prosocial behavior; blood donations; social recognition; natural field experiment; social media; WhatsApp